2020
DOI: 10.21203/rs.3.rs-130714/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual Effects of Silibinin on Human Pancreatic Cancer Cells

Abstract: Background Silibinin is a flavonoid with antihepatotoxic properties, and exhibits pleiotropic anticancer effects. However, the molecular mechanisms responsible for its anticancer actions in pancreatic cancer cells, and the effects on such cells and normal pancreatic cells, remain unclear. The objective of this study was to determine the effect of silibinin on human pancreatic cancer cells and normal ductal cells.Methods Human pancreatic cancer cells (MIA PaCa-2 and PANC-1) and normal ductal cells (hTERT-HPNE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Silibinin increased exogenous p53 levels in normal ductal cells while reducing the expression of stemness-related genes. Furthermore, it increased Ki-67 levels in pancreatic cancer cells but decreased them in normal ductal cells ( Lee et al, 2020 ).…”
Section: Role Of Silibinin In Cancermentioning
confidence: 99%
“…Silibinin increased exogenous p53 levels in normal ductal cells while reducing the expression of stemness-related genes. Furthermore, it increased Ki-67 levels in pancreatic cancer cells but decreased them in normal ductal cells ( Lee et al, 2020 ).…”
Section: Role Of Silibinin In Cancermentioning
confidence: 99%
“…For example, in pancreatic cancer it promotes growth arrest and apoptosis (see Table 6) and decreases CD44 signaling. However, Lee et al 408 found that in addition to the antitumoral actions, silymarin also upregulated cancer stemness-related genes, namely TWIST1, Snail, and c-Jun. At the same time, it decreased p53 wild type and increased Ki-67 (a marker of proliferation).…”
Section: The Main Problems With Silymarinmentioning
confidence: 99%